Drainage of Flooded Rice Soil Influence the Residue Carbon Contribution in Methane Emissions - Tariq, Azeem; Jensen, Lars Stoumann; Sander, Björn Ole; Tourdonnet, Stephane de; Ambus, Per Lennart; Hữu Thành, Phan; Van Mai, Trinh; Neergaard, Andreas de (2017)
The Climate Food and Farming (CLIFF) Research Network is an international research network that helps to expand young researchers' knowledge and experience working on climate change mitigation in smallholder farming. CLIFF provides grants for selected doctoral students to work with CGIAR researchers affiliated with the Standard Assessment of Mitigation Potential and Livelihoods in Smallholder Systems (SAMPLES) project. This presentation is Drainage of Flooded Rice Soil Influence the Residue Carbon Contribution in Methane Emissions by Phan Hữu Thành, at the Institute for Agricultural Environment, Vietnamese Academy of Agriculture Sciences, in Hanoi, Vietnam.